Biomonitorization of iron accumulation in the substantia nigra from Lewy body disease patients. (2017) - Fernández, Belén; Ferrer, Isidro; Gil, Fernando; Hilfiker, Sabine
Graphical abstract: Highlights: Sensitive detection of total iron content from cells, rodent and human brain extracts. There are regional differences in iron concentrations in rodent and human brain. Iron dyshomeostasis in the substantia nigra correlates with Lewy body disease. Iron imaging studies may aid in clinical diagnosis and/or serve as biomarker for disease progression. Abstract: Iron levels in the healthy human brain are known to be high in certain areas such as the substantia nigra (SN), and increase further with age. In addition, there is some evidence for a further increase in iron load in the SN of Parkinsońs disease (PD) patients as compared to controls, which correlates with motor disability. Here, we have analyzed total iron levels in cells as well as mouse and human brain samples by atomic absorption spectroscopy (AAS). Our data indicate that iron load is more pronounced in cells with dopaminergic features. Moreover, region-specific differences in iron load reflecting those in the human brain were detected in rodent brains as well. Whilst altered iron load was not observed in other regions also affected in PD patients, we report a significant increase in iron load in the SN of Lewy body disease patients as compared to Alzheimeŕs disease (AD) patients or controls, which correlates with neurodegeneration in this brain area.